APRESENTAÇÃO - Novaes da Silva, José Antonio; Canavarro Benite, Anna Mª; Barbosa de Sá Figueiredo, Mércia Otaviana; Camargo Vianna, Cintia (Revista da Associação Brasileira de Pesquisadores/as Negros/as (ABPN), 2020)
Apresentação